How to use patient-reported outcomes measures with other clinical measurements in clinical reports - Rodrigues, J; Neblett, C (SAGE Publications, 2018)
Clinical outcomes in hand surgery can be measured and reported in many ways, including those performed under controlled conditions by clinicians, such as grip strength or finger joint angles, and assessments of function that involve completing specific simulated daily tasks. Patient-reported outcome measures (PROMs) are another group of outcome measures that are defined as reports obtained directly from the patient and typically involve questionnaires. PROMs can assess hand function, health status, and patient satisfaction. The use of PROMs is rising in scientific articles in hand surgery. However, PROMs are not necessarily a panacea. Here, we will aim to rationalize the choice of outcome measures using our current understanding of PROMs in hand surgery.